Družbeni strahovi med znanostjo in kulturnim bojem - Vidmar, Ksenija H. (Ars et humanitas, 2021)
This article looks at the rise of the conspiracy theories during the COVID-19 pandemic. Current social research on conspiracy theories points to two major factors which underline the spread and appeal of conspiracy thinking: social media and the rise of alternative truths; and the rising distrust in science. Both factors, no doubt, contribute to the current "epistemological crisis", but cannot successfully explain a broader "anti-Enlightenment turn". In order to better understand the appeal of conspiracy theories, the author brings into the picture the current rise of radical populism. A comparative look at the two structures of feeling, she argues, allows us to better understand the role of the neoliberal state which has triggered many social fears and, by under-mining the idea of the common good, opened up a ground for the polarization of communities.
Keywords: alternative truths; alternativne resnice; anti-Enlightenment; conspiracy theories; epidemics; epidemije; neoliberalism; neoliberalizem; populism; populizem; protirazsvetljenstvo; teorije zarote